2006
DOI: 10.1093/ndt/gfl432
|View full text |Cite
|
Sign up to set email alerts
|

Bioelectrical impedance can be used to predict muscle mass and hence improve estimation of glomerular filtration rate in non-diabetic patients with chronic kidney disease

Abstract: ALM(BIA) provides a clinically obtainable and valid method to predict muscle mass in patients with CKD, and using ALM(BIA) improves the estimation of GFR(inu). Researchers developing future GFR estimation equations should consider including ALM(BIA).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
37
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(38 citation statements)
references
References 23 publications
0
37
0
1
Order By: Relevance
“…Considering prior studies in CKD patients [10,11], our results are plausible but the magnitude of the effect needs to be examined in future investigations. While the homogeneity of the subjects may be considered a strength of the study, it may also limit the generalizability of our findings.…”
Section: Discussionmentioning
confidence: 70%
See 3 more Smart Citations
“…Considering prior studies in CKD patients [10,11], our results are plausible but the magnitude of the effect needs to be examined in future investigations. While the homogeneity of the subjects may be considered a strength of the study, it may also limit the generalizability of our findings.…”
Section: Discussionmentioning
confidence: 70%
“…Another study carried out in Sweden [9] showed an improvement in the accuracy of eGFR when calculated lean mass was included in the prediction equation. None of these studies have employed the CKD-EPI equation and are limited to relatively small groups of patients or special populations [5,6,7,8,9,10,11,12]. Our study suggests that body composition may also be of importance in the general population but the effect may be of lesser magnitude than in these selected populations.…”
Section: Discussionmentioning
confidence: 78%
See 2 more Smart Citations
“…Because the serum creatinine value is the balance of the release from skeletal muscle and removal by the kidneys, both muscle mass and renal function are important determinants. Recent studies have shown that anthropometric/demographic variables, such as age, gender, height, and weight, may not adequately account for variance in muscle mass, and that measures of muscle mass, which can be clinically obtainable (24), may improve the estimation of GFR (25). Third, owing to the cross-sectional nature of the current study, we cannot determine whether or not elevation of eGFR in smokers modulates long-term renal prognosis.…”
Section: Discussionmentioning
confidence: 83%